Immobilized Supramolecular Systems as Efficient Synzymes for CO2 Activation and Conversion. (5th January 2022) - Esteve, Ferran; Escrig, Adrian; Porcar, Raul; Luis, Santiago V.; Altava, Belén; García‐Verdugo, Eduardo
Abstract: Supramolecular catalysis can provide distinct advantages for the catalytic conversion of CO2 into carbonates by cycloaddition to epoxides. For example, the absence of metals in the catalytic site, and the easy design for optimization. The incorporation of multiple functionalities in pseudopeptidic macrocycles with a pendant arm allows catalytic systems to be obtained where halide anions (nucleophilic activating agents for epoxides), hydrogen bond acceptor sites (activating agents for epoxides and stabilizing sites for anionic intermediates), and amine groups (Lewis basic sites for activating CO2 ) are in proximity. This allows a high activity in the cycloaddition of CO2 to styrene oxide under mild conditions (turnover number (TON) = 900, CO2 balloon, 100 °C, 5 h). The primary amino groups in the arm facilitate the immobilization of these macrocyclic structures in cross‐linked polymeric matrices containing ammonium halide fragments. Such multifunctional insoluble polymers afford excellent catalytic results with high TON and turnover frequency values and remarkable productivities (>10 gprod  gresin −1  h −1 ). This activity is maintained for a variety of epoxides and is retained after several catalytic runs. Their performance is significantly higher than those reported for most heterogenous supramolecular catalytic systems for CO2 transformation into carbonates. Abstract : A novel series of macrocyclic pseudopeptides prove to be active organocatalysts for the cycloaddition of CO2 to epoxides. Immobilization of the two catalytically active components on solid supports leads to excellent and reusable catalysts. The confinement within the hydrophobic polymeric matrix allows for stronger supramolecular interactions between the active species and the substrates/intermediates, mimicking enzymatic behavior.